Eliminating Factor H-Binding Activity of Borrelia burgdorferi CspZ Combined with Virus-Like Particle Conjugation Enhances Its Efficacy as a Lyme Disease Vaccine - Marcinkiewicz, Ashley L.; Lieknina, Ilva; Kotelovica, Svetlana; Yang, Xiuli; Kraiczy, Peter; Pal, Utpal; Lin, Yi-Pin; Tars, Kaspars (Frontiers in Immunology, 2018)
The spirochete Borrelia burgdorferi is the causative agent of Lyme disease, the most common tick-borne disease in the US and Europe. No potent human vaccine is currently available. The innate immune complement system is vital to host defense against pathogens, as complement activation on the surface of spirochetes results in bacterial killing. Complement system is inhibited by the complement regulator factor H (FH). To escape killing, B. burgdorferi produces an outer surface protein CspZ that binds FH to inhibit complement activation on the cell surface. Immunization with CspZ alone does not protect mice from infection, which we speculate is because FH-binding cloaks potentially protective epitopes. We modified CspZ by conjugating to virus-like particles (VLP-CspZ) and eliminating FH binding (modified VLP-CspZ) to increase immunogenicity. We observed greater bactericidal antibody titers in mice vaccinated with modified VLP-CspZ: A serum dilution of 1:395 (modified VLP-CspZ) vs 1:143 (VLP-CspZ) yielded 50% borreliacidal activity. Immunizing mice with modified VLP-CspZ cleared spirochete infection, as did passive transfer of elicited antibodies. This work developed a novel Lyme disease vaccine candidate by conjugating CspZ to VLP and eliminating FH-binding ability. Such a strategy of conjugating an antigen to a VLP and eliminating binding to the target ligand can serve as a general model for developing vaccines against other bacterial infectious agents.